Design of the GAGG scintillator for High Active Liquid Waste. (May 2019) - Sekine, Megumi; Matsuki, Takuya; Suzuki, Satoshi; Yasuda, Takeshi; Tsutagi, Koichi; Nakamura, Hironobu; Tomikawa, Hirofumi
Abstract: In a reprocessing facility, it is required to develop a detector which can monitor plutonium (Pu) amount in the Pu solution containing the Fission Product (FP) in order to strengthen the safeguards capability. In order to investigate gamma rays which is applicable for Pu monitoring for High Active Liquid Waste (HALW), Ce:GAGG (Ce:Gd3 Al2 Ga3 O12 ) scintillator which can measure a wide range of energy at high radiation dose rate and has relatively high resolution was newly designed and developed in deal with aim for monitoring of Pu quantity. Gamma ray measurement was conducted to HALW in the concrete cell by the designed detector, and it was confirmed that Eu-154 was detected using GAGG scintillator in HALW. In this paper, detector design, results of gamma ray spectra measurement, applicability evaluation to Pu monitoring and the future plan are presented.